Prohibition of recording hearings for the media in Ecuador against the principle of publicity - Macanchí Procel, Joffre Eduardo; Quezada Bravo, Alan Eduardo; Mendieta Sarmiento, Patricia Angelita (Revista Universidad de Guayaquil, 2025)
Advertising has been part of the Ecuadorian Legal System through the Constitution of the Republic of Ecuador, the General Organic Code of Processes, Organic Code of the Judicial Function and Comprehensive Criminal Organic Code, hereinafter CRE, COFJ, COGEP, COIP respectively, establishing as an object of study the prohibition that social media have as they cannot photograph, film and transmit the hearings. In this research, a qualitative approach and documentary, hermeneutical and exegetical methods were used and it was proven that this prohibition on the media is a limit to the principle of advertising, since the two aspects were not satisfied with the external one, in addition opposed the new model of open justice, which seeks to ensure that by recording and transmitting the hearings through the social media the citizen is aware of the actions of the judiciary and why not say that by reforming the COFJ, the COGEP and the COIP Regarding the permissibility of recording and transmitting hearings by professionals who carry out this communication activity, it allows to mitigate the existence of parallel trials by the news media.